2001
DOI: 10.1046/j.1523-1747.2001.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Increases Tropoelastin mRNA Expression in the Epidermis of Human Skin In Vivo

Abstract: Photoaged skin contains elastotic materials in the upper reticular dermis. This phenomenon is commonly known as solar elastosis. Little is known about the mechanisms leading to the accumulation of elastotic materials in photoaged skin, however. In this study, it was demonstrated that ultraviolet irradiation induced tropoelastin mRNA expression in the keratinocytes of human skin in vivo and also in cultured human keratinocytes by in situ hybridization and reverse transcriptase polymerase chain reaction. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 21 publications
6
71
0
Order By: Relevance
“…Moreover, Weiss [55] reported a reduction in elastin production with age or as a result of damage caused by solar radiation. However, the occurrence of elastosis assumes an increase in elastic material in the photoaged skin, as observed in other studies [22,56]. This seemingly paradoxical situation should be analysed by considering the non-functionality of the fibres present in elastosis.…”
Section: Elastin Role On Photoageingmentioning
confidence: 71%
“…Moreover, Weiss [55] reported a reduction in elastin production with age or as a result of damage caused by solar radiation. However, the occurrence of elastosis assumes an increase in elastic material in the photoaged skin, as observed in other studies [22,56]. This seemingly paradoxical situation should be analysed by considering the non-functionality of the fibres present in elastosis.…”
Section: Elastin Role On Photoageingmentioning
confidence: 71%
“…Another prominent feature of photoaged skin is solar elastosis. 10 Some studies showed that solar elastosis could relate with increased tropoelastin gene expression 11 or an increased expression of fibrillin in the photodamaged skin. 12 In addition, degradation of elastic fibers by UV-induced MMP-12 might contribute to the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be related to the increased production of elastic fibers, which consist of elastin and fibrillin-rich microfibrils. 11,12 The degradation of elastin by MMP-12 (human macrophage metalloelastase) may also contribute to the development of solar elastosis in photoaged skin. 13 In the present study, we examined pre-and post-ALA-PDT specimens for AK and determined whether ALA-PDT induced histologic changes reversing the destructive connective tissue events associated with photoaging.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Reported in both in vivo and in vitro, UVB irradiation induces tropoelastin gene and protein expression in fibroblasts and keratinocytes, resulting in an aberrant accumulation of dermal elastic fibers and elastin content. 5,8,10,11,20 On the other hand, it has been reported that the degeneration of these fibers in chronologically and/or photoaged skin stems from an increase in matrix metalloproteinase-12 (MMP-12) and/or elastase, an elastin-degrading enzyme that is produced and secreted by dermal fibroblasts. [21][22][23][24] To date, the mechanisms underlying the alteration of elastin fibers in photoaged skin including their production, accumulation, and degradation are not fully understood.…”
mentioning
confidence: 99%